SIMULASI GERAK PARTIKEL BERMUATAN DALAM PENGARUH MEDAN LISTRIK DAN INDUKSI MAGNET MENGGUNAKAN MATLAB VERSI 7.1 - Azam, Much.; Kusbramanto, Tomy; Endro Suseno, Jatmiko (BERKALA FISIKA, 2007)
Charged particle motion under external electric, magnetic induction, and electric-magnetic induction field simulation program has been made using MATLAB ver. 7.1 to get the visual description of charged particle motion. The simulation program is made based on non relativistic Lorentz equation.  Each of charged particle’s position and velocity components, which is moved under external electric and or induction magnetic filed(s), is numerically computed using forth order Runge-Kutta method and be made visible by the simulation program. Proper test of the simulation program is made using known text book as the reference. Simulation results which made of 3D profile of charged particle’s motion path  and  each velocity components has already shown that it have good relationship with the known text book   Keywords : charged particle motion, position, velocity